Emergency nurses' knowledge and experience with the triage process in Hunan Province, China. (November 2017) - Hammad, Karen; Peng, Lingli; Anikeeva, Olga; Arbon, Paul; Du, Huiyun; Li, Yinglan
Highlights: Half of respondents received dedicated training prior to commencing triage role. Half of respondents reported using formal triage scales when conducting triage. There is considerable variation in triage practice and training in Changsha, China. Abstract: Introduction: Triage is implemented to facilitate timely and appropriate treatment of patients, and is typically conducted by senior nurses. Triage accuracy and consistency across emergency departments remain a problem in mainland China. This study aimed to investigate the current status of triage practice and knowledge among emergency nurses in Changsha, Hunan Province, China. Method: A sample of 300 emergency nurses was selected from 13 tertiary hospitals in Changsha and a total of 193 completed surveys were returned (response rate = 64.3%). Surveys were circulated to head nurses, who then distributed them to nurses who met the selection criteria. Nurses were asked to complete the surveys and return them via dedicated survey return boxes that were placed in discreet locations to ensure anonymity. Results: Just over half (50.8%) of participants reported receiving dedicated triage training, which was provided by their employer (38.6%), an education organisation (30.7%) or at a conference (26.1%). Approximately half (53.2%) reported using formal triage scales, which were predominantly 4-tier (43%) or 5-tier (34%). Conclusions: The findings highlight variability in triage practices and training of emergency nurses in Changsha. This has implications for the comparability of triage data and transferability of triage skills across hospitals.